Zinc protoporphyrin levels have added value in the prediction of low hemoglobin deferral in whole blood donors. Issue 8 (26th November 2012) - Baart, A. Mireille; de, Wim L.A.M.; Moons, Karel G.M.; Atsma, Femke; Vergouwe, Yvonne
<x xml:space="preserve">Abstract</x> Background Increased zinc protoporphyrin (ZPP) levels can indicate iron deficiency and may be predictive for low hemoglobin (Hb) deferral in blood donors. Prediction models for Hb deferral in whole blood donors have already been developed. In this study, we examined if addition of ZPP to these prediction models improves risk estimation of Hb deferral. Study Design and Methods This study included 4598 Dutch whole blood donors. Information on ZPP levels measured at the previous visit was added to the existing prediction models to estimate the risk of Hb deferral. Models were compared using the following measures: concordance (c)‐statistic, continuous net reclassification improvement (NRI), and clinical net benefit (NB). Results Seventy‐six male donors (2.9%) and 69 female donors (3.5%) were deferred because of a low Hb level. Previous ZPP level was associated with risk of Hb deferral (odds ratio for interquartile range of previous ZPP level, men 2.0 [95% confidence interval CI, 1.7‐2.3]; women 2.2 [95% CI, 1.9‐2.4]) in a multivariable risk model. Addition of ZPP into the models resulted in an increase of the c‐statistic from 0.93 to 0.94 for men and from 0.80 to 0.85 for women. The added value of ZPP was confirmed by measures of clinical usefulness. NRI for men was 0.42, and for women, 0.56. At relevant threshold probabilities between 10 and 15%, NB was higher for models considering ZPP. Conclusion This study shows that ZPP measurements obtained at the previous visit may have added value in the risk prediction of Hb deferral in whole blood donors.